PSYCHOLOGICAL ASSESSMENT OF THE ORIENTATION OF STUDENTS TO THE PROFESSION (Scientific journal of the Fergana State University, 2024)
This article reflects on the psychological factors of professional orientation of students, after all, the choice of a profession occupies an important place in the life of every person. The earlier, purposefully, and responsibly this work is initiated, the more positive results it produces. In order to choose the right profession, it is necessary to have a deep understanding of as many specialties as possible. Because the more complete and objective education a person has in their chosen profession, the less likely they are to commit an error. Choosing a profession is the most important step in a person's life. Through interactive surveys and hands-on activities, students find answers to questions about the concept of a profession and professions. In the future, they begin to have an idea of the professions they want to master. A profession is a consciously chosen path of activity. The chosen professions of students should correspond to their abilities, interests, character traits. Because the chosen profession should benefit not only their own, but also Society. The article highlights the assumption of research on the topic of determining the orientation of psychologist scientists to the profession of young people and their orientation according to their interests, the Russian psychologist E.A.Klimov The results and conclusions of the study of the methodology of the “differential diagnostic survey” (DDS) developed by were written.